The Influence of Brand Image, Product Innovation, and Green Marketing on Customer Loyalty Through Perception of Green Products - Suhendar, Andri; Widayati, Christina Catur (Dinasti International Journal of Digital Business Management, 2025)
This study aims to analyze the effect of brand image, product innovation, and green marketing on customer loyalty through the perception of environmentally friendly products. This research was conducted at Horison Nindya Hotel Semarang with a quantitative approach. The data were analyzed using PLS-SEM technique through SmartPLS 4.0 software. The results showed that product innovation and green marketing had a significant effect on green product perceptions. Green product perception also has a significant effect on customer loyalty. In addition, brand image, product innovation, and green marketing have a significant effect on customer loyalty. However, brand image has no significant effect on green product perception. These findings provide theoretical implications in strengthening the application of green consumer behavior (Peattie & Crane, 2005; Ajzen, 2020).